Associations Between Genome-wide Gene Expression and Ambient Nitrogen Oxides. Issue 3 (May 2017) - Mostafavi, Nahid; Vlaanderen, Jelle; Portengen, Lutzen; Chadeau-Hyam, Marc; Modig, Lars; Palli, Domenico; Bergdahl, Ingvar A.; Brunekreef, Bert; Vineis, Paolo; Hebels, Dennie G. A. J.; Kleinjans, Jos C. S.; Krogh, Vittorio; et al.
Abstract : Background: We hypothesize that biological perturbations due to exposure to ambient air pollution are reflected in gene expression levels in peripheral blood mononuclear cells. Methods: We assessed the association between exposure to ambient air pollution and genome-wide gene expression levels in peripheral blood mononuclear cells collected from 550 healthy subjects participating in cohorts from Italy and Sweden. Annual air pollution estimates of nitrogen oxides (NO x ) at time of blood collection (1990–2006) were available from the ESCAPE study. In addition to univariate analysis and two variable selection methods to investigate the association between expression and exposure to NO x, we applied gene set enrichment analysis to assess overlap between our most perturbed genes and gene sets hypothesized to be related to air pollution and cigarette smoking. Finally, we assessed associations between NO x and CpG island methylation at the identified genes. Results: Annual average NO x exposure in the Italian and Swedish cohorts was 94.2 and 6.7 µg/m 3, respectively. Long-term exposure to NO x was associated with seven probes in the Italian cohort and one probe in the Swedish (and combined) cohorts. For genes AHCYL2 and MTMR2, changes were also seen in the methylome. Genes hypothesized to be downregulated due to cigarette smoking were enriched among the most strongly downregulated genes from our study. Conclusion: This study provides evidence of subtle changes in gene expression related to exposure to long-term NO x . On a global level, the observed changes in the transcriptome may indicate similarities between air pollution and tobacco induced changes in the transcriptome. Abstract : Supplemental Digital Content is available in the text.